2020
DOI: 10.3390/jcm9051444
|View full text |Cite
|
Sign up to set email alerts
|

The Needs and Experiences of Post-Treatment Adolescent and Young Adult Cancer Survivors

Abstract: (1) Background: Adolescents and young adults (AYAs) who have been diagnosed with and treated for cancer have unique healthcare needs, but more research is needed to inform developmentally targeted cancer care for this population. The purpose of the current analyses was to describe the physical and psychosocial concerns and experiences of AYA cancer survivors during the post-treatment phase. (2) Methods: A national survey was conducted by the Canadian Partnership Against Cancer to evaluate the experiences and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 64 publications
4
67
0
15
Order By: Relevance
“…The complex mechanisms underlying these sequelae make them difficult to prevent and treat, often leading to chronic impairments in physical functioning and quality of life [ 4 ]. For example, highly burdensome health issues in AYAs like cancer-related cardiovascular disease [ 5 ], fatigue [ 6 ] and psychological distress [ 7 ] are known to be caused and influenced by interactions between cancer-, behavioural- and life stage-related physical and psychosocial factors [ 8 12 ]. Importantly, there is a growing body of evidence that multi-system interventions, like exercise, are among the most effective therapies to mitigate and reverse adverse effects associated with cancer and its treatment [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complex mechanisms underlying these sequelae make them difficult to prevent and treat, often leading to chronic impairments in physical functioning and quality of life [ 4 ]. For example, highly burdensome health issues in AYAs like cancer-related cardiovascular disease [ 5 ], fatigue [ 6 ] and psychological distress [ 7 ] are known to be caused and influenced by interactions between cancer-, behavioural- and life stage-related physical and psychosocial factors [ 8 12 ]. Importantly, there is a growing body of evidence that multi-system interventions, like exercise, are among the most effective therapies to mitigate and reverse adverse effects associated with cancer and its treatment [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 13,258 completed surveys, 575 respondents were AYAs between the ages of 18 and 34. Further detail regarding the survey development, sample selection, and survey dissemination is available in Fitch et al, 2018 [24], and Jones et al, 2021 [20].…”
Section: Survey Datamentioning
confidence: 99%
“…Despite calls for the development of specialized follow-up care and survivorship programs for this unique population [18][19][20][21], many AYA survivorship issues continue to be poorly managed [18], leading to unmet supportive care needs and concerns. Research on AYA cancer survivors remains underrepresented in the literature [18], and there is little evidence to inform the care of AYAs survivors, particularly in the follow-up survivorship period, when unmet needs are often at their highest [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer and cancer-related treatment are associated with a myriad of deleterious short-and long-term side effects that can negatively impact physical function and accelerate functional decline [7]. Notably, a recent study on AYA cancer survivors indicated a high rate of physical concerns (88%) and emotional concerns (79%), yet fewer than 50% reported that their concerns have been addressed by their healthcare team [8].…”
Section: Introductionmentioning
confidence: 99%